Estudo comparativo das leis de uso e ocupação do solo e proposta de adequação para o caso de Fortaleza-CE - Abreu, Cristiane Baima de (2009)
The Law of Use and Occupation of Land – LUOL is part of the urban cities legislation, defines rules and standards related to zoning, activities, use and occupation, road system, police and administrative power. This instrument of municipal urbanistic planning details the local structure proposed in the Urban Master Plan, which should effectively follow the city’s growth. The last amendment of the LUOL of Fortaleza was published in 1998, more than ten years have passed by without its update considering the actual urban context of the city. The aim of the present work is to make a comparative analysis of several LUOL directive from different Brazilian cities, in order to propose improvements and adjustments to the current LUOL of Fortaleza city. The cities LUOL(s) to be analyzed were selected according to a statistical technique called cluster analysis, multivariate analysis. During this research a literature review was performed, starting from the Federal Constitution of Brazil from 1988, through the Constitution of the State of Ceará, and other Federal and Municipal Laws, in order to provide a basis for the topics reviewed. Therefore, not only is necessary to update the urban standards, but also that administrative managers implement them and create ways to make their resolutions to be followed by the population. This work will serve as a tool to help technical personnel from local the planning department, specifically, on the update the LUOL of Fortaleza, mainly considering that there are few studies about it.